The nature of accessibility studies - Greco, Gian Maria (Journal of Audiovisual Translation, 2018)
Accessibility has come to play a pivotal role on the world’s stage, gradually pervading different aspects of our lives as well as a vast range of fields, giving rise to a plethora of fruitful new ideas, methods and models, and becoming an ever more key issue within a process that is reshaping the very fabric of society. The ubiquitous effects of accessibility have led to the emergence of a new research field, namely accessibility studies (AS). This paper presents both the path that has led towards the emergence of AS as well as the distinctive features of this new field. AS is defined as the field concerned with the investigation of accessibility processes and phenomena, and the design, implementation and evaluation of accessibility-based and accessibility-oriented methodologies. The analysis is carried out mainly, though not exclusively, in reference to media accessibility (MA), as it is one of the most mature areas in which the process of the formation of AS has been taking place. It concludes by arguing that AS is a timely field that addresses the most pressing issues our society is facing nowadays and appealing to MA to embrace its identity as an area of AS.